Implementasi Pendidikan Karakter Religius dalam Pembentukan Kepribadian Siswa SD Negeri 101928 Rantau Panjang - Ananda, Dhea Dwi; Malinda, Leni; Hidayat, Wahyu (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to examine the influence of domino card learning media on student learning outcomes in the topic of plant structure and function for fourth-grade students at SD Negeri 101928 Rantau Panjang and SD Negeri 101961 Timbang Deli. The research employs a quasi-experimental quantitative approach. It was conducted at SD Negeri 101961 Timbang Deli, involving two classes of 20 students each: an experimental class using domino card media and a control class without the media. Data collection was carried out through pretests and posttests to assess student performance. The results showed that the experimental class, which utilized domino card media, achieved the highest score of 92, whereas the control class attained a highest score of 88. These findings indicate that the use of domino card learning media positively impacted the science learning outcomes of fourth-grade students at SD Negeri 101961 Timbang Deli.